EDUCATION IN THE RUSSIAN ARCTIC: OPTIMIZATION RESULTS AND DEVELOPMENT PRIORITIES - Ekaterina E. Toropushina (Север и рынок: формирование экономического порядка)
Education forms the foundation of social development, improves quality of life, and supports the creation of sustainable communities. It does so by delivering essential services, fostering territorial cohesion and social integration, developing human and social capital, stimulating economic growth, and laying the groundwork for higher income and better employment opportunities. Additionally, it boosts competitiveness and productivity. Ensuring access to quality primary education at the place of residence, along with equitable opportunities for vocational training and higher education, is critical for the sustainable development of the Arctic territories. This study contributes to the scientific discourse on the development of human resources and educational infrastructure in the Russian Arctic, continuing the author’s publication series on the social infrastructure of the Arctic. The article aims to examine changes in human resources and infrastructure within the education system of the Russian Arctic over the past two decades and to propose directions for its further development. The research employs methods such as content analysis, logical reasoning, and comparative analysis. Findings indicate that, in recent years, the education sector in the Russian Arctic has undergone optimization through mergers and closures of institutions and reductions in personnel, leading to increased polarization in the sector. Addressing these challenges requires policy improvements to ensure access to quality primary education not only in urban centers but also in sparsely populated Arctic areas. There is also a need to expand vocational training opportunities directly within Arctic regions, codify existing initiatives, and integrate them with new educational projects and programs. The practical significance of this research lies in its potential application in public administration for advancing the education system in the Russian Arctic. Future research in this area should focus on in-depth analyses of international practices, studies of wages and the private education sector, and evaluations of the quality of educational programs.